Physiological changes occurred in buffalo bulls (Bubalus bubalis) subject to thermal stress - Chacur, M. G.M.; Oba, E. [UNESP]; Ferreira, J. C.P. [UNESP]; Velloso, N. M. [UNESP] (My University, 2010)
This study aimed to evaluate the physiological changes in buffalo bulls subjected to heat stress for a period of 54 days. We used eight male crossbred (Murrah × Mediterranean) with three years old. The animals were housed in a climate chamber and divided into two groups: control group (CG), wich was subjected to a temperature of 22.5 ° C, and heat stressed group (SG), whose temperature was 39° C. During this period, there was blood sampling of animals at 8:00 am and 2:00 pm in the first three days and after, weekly at the same times, aiming at the hemogram and reproductive hormones analysis. In order to study the circadian variation, nine blood samples were taken every six hours. Having completed this phase, the animals were orchiectomized and the testicular histology was performed. Statistical analysis of the values of the hemogram revealed a significant difference between treatments for concentrations of hemoglobin, fibrinogen, neutrophils and eosinophils, being that these values were higher in animals of SG. In both groups, concentrations of androstenedione and testosterone were significantly lower at about 8 am in relationship to 2 pm, with no statistical difference between treatments. About the circadian rhythm of hormones, no significant difference in testosterone concentrations between treatments, with peak at 2 pm and minimum at 2 am. The thermal factor did not result in significant differences in diameter of seminiferous tubules between SG and CG in testicular histology.
Keywords: Buffalo bulls; Physiology; Reproduction; Thermal stress